Assistance in determining the cost of production, selling prices, and preparing financial reports in Sungai Luar Village - Wardah, Siti Wardah (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Islam Indragiri, 2022)
This research assistance in determining the cost of production, selling prices, and preparing Financial Statements in the Context of Increasing Competitiveness After the Covid-19 Pandemic in Sungai Luar Village. The purpose of this study is to assist village community business actors in how determining the cost of production and selling prices as well as how to prepare financial reports to increase competitiveness after the COVID-19 pandemic in Sungai Luar village. The methods used are interviews, observations, surveys, direct material delivery, simulations, and discussions. From this research, the business has the enthusiasm and effort to develop. However, it lacks adequate knowledge and understanding of determining the cost and selling price and financial preparation. There are several obstacles faced by the community of Sungai Luar village, the lack of human resources who can determine the cost of production and selling price in running a business and the lack of time to understand or learn how to determine the cost of production, and selling price in a business. The lack of the time needed to make financial reports on the business because the time there is more for operational activities to get started